2003
DOI: 10.1093/jee/96.6.1905
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogenic Potential in Cassava and Its Influence on a Generalist Insect Herbivore Cyrtomenus bergi (Hemiptera: Cydnidae)

Abstract: The hypothesis that cyanogenic potential in cassava is a defense mechanism against arthropod pests is one of the crucial questions relevant to current efforts to reduce or eliminate cyanogenic potential (CNP) in cassava. The generalist arthropod Cyrtomenus bergi, which attacks cassava roots, was used in a bioassay relating oviposition and survival to CNP, concentration of nonglycosidic cyanogens, and linamarase (beta-glycosidase) activity in twelve selfed cassava siblings and their parental clone, which has se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…In a similar series of experiments, we determined that the cyanide potential was raised in 6-week-old cassava plants following administration of nitrogen. The cyanide potential in leaves and tubers from the same plant may also differ (de Bruijn, 1973;Riis et al, 2003). To minimize the experimental work to identify a transgenic cassava line that does not contain cyanogenic glucosides in leaves and tubers, it was desirable to be able to define the earliest plant stage and the type of plant tissue suitable for robust screening to avoid growing all transgenic lines to the tuber stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar series of experiments, we determined that the cyanide potential was raised in 6-week-old cassava plants following administration of nitrogen. The cyanide potential in leaves and tubers from the same plant may also differ (de Bruijn, 1973;Riis et al, 2003). To minimize the experimental work to identify a transgenic cassava line that does not contain cyanogenic glucosides in leaves and tubers, it was desirable to be able to define the earliest plant stage and the type of plant tissue suitable for robust screening to avoid growing all transgenic lines to the tuber stage.…”
Section: Discussionmentioning
confidence: 99%
“…Riis et al (2003) have investigated pest attack on cassava varieties possessing different cyanide potential and concluded that a larger pest outbreak or damage level in acyanogenic clones was not to be expected. Insect generalists such as the grasshopper Zonocerus variegatus and the burrowing bug Cyrtomenus bergi do not accept high levels of cyanogenic glucosides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the levels of cyanogenic glycosides in cassava roots are generally lower than that in the leaves and stems [21,22]. Cassava roots have been reported to contain cyanide content of 10-00 mg/kg of dry mater [23] and the leaves were reported to contain 3-1300 cyanide equivalents/kg of dry mater [24].…”
Section: Cassavamentioning
confidence: 99%
“…Basic biological aspects are well known (García and Bellotti 1980 ;Riis et al 2005b ), as well as information about behavior, population dynamics, and food preference (Riis 1997 ;Riis et al 2005a , b ). Chemical, biological, and cultural control was discussed in several works (e.g., Bellotti and Riis 1994 ;Calcedo and Bellotti 1994 ;Sánchez and Bellotti 1997 ;Barberena and Bellotti 1998 ;Riis et al 2003 ;Jaramillo et al 2005 ).…”
Section: Key To Some Of the Genera Of Cydninae: Geotomini Of The Neotmentioning
confidence: 99%